The Short-Term Impact of COVID-19 on Labor Markets, Poverty and Inequality in Brazil. (IMF Working Papers; Working Paper ;, 2021)
We document the short-term impact of the COVID-19 pandemic on the Brazilian labor market focusing on employment, wages and hours worked using the nationally representative household surveys PNAD-Continua and PNAD COVID. Sectors most susceptible to the shock because they are more contact-intensive and less teleworkable, such as construction, domestic services and hospitality, suffered large job losses and reductions in hours. Given low income workers experienced the largest decline in earnings, extreme poverty and the Gini coefficient based on labor income increased by around 9.2 and 5 percentage points, respectively, due to the immediate shock. The government's broad based, temporary Emergency Aid transfer program more than offset the labor income losses for the bottom four deciles, however, such that poverty relative to the pre-COVID baseline fell. At a cost of around 4 percent of GDP in 2020 such support is not fiscally sustainable beyond the short-term and ended in late 2020. The challenge will be to avoid a sharp increase in poverty and inequality if the labor market does not pick up sufficiently fast in 2021.